Application of Lex Superior Principle in Shareholders General Meeting at Public Companies: South Jakarta District Court Case NO. 91/PDT. P/2024 - Sembiring, Andryan Esra; Suprapti, Endang; Bangun, Suriadi (Jurnal Indonesia Sosial Sains, 2025)
Law No. 40 of 2007 is a Lex Superior for Limited Liability Companies in the Implementation of the General Meeting of Shareholders (GMS), as regulated in Chapter VI articles 75 to 91. When the Limited Liability Company becomes a Public Company, the holding of the GMS is subject to the Financial Services Authority Regulation (POJK) No. 15 of 2020, so that POJK No. 15 of 2020 is an inferior Legi to Law No. 40 of 2007. In the decision of the Panel of Judges of the South Jakarta District Court No. 91/Pdt.P/2024/PN Jkt on the application to reduce the number of quorums in the Extraordinary General Meeting of Shareholders at PT Exploitasi Energi Indonesia, Tbk, the Panel of Judges made a determination decision granting the application of PT Exploitasi Energi Indonesia, Tbk, with legal considerations: (a) The Articles of Association of PT Exploitasi Energi Indonesia, Tbk Article 22 letter F state that in the event that the quorum of the Second GMS is not reached, then at the request of the Company, the quorum is determined by the Chairman of the District Court whose territory includes the Company's domicile (b) Article 86 paragraph 5 of Law No. 40 of 2007 states that in the event that the quorum of the Second GMS as referred to in paragraph 4 is not reached, The Company may request the Chairman of the District Court whose jurisdiction includes the Company's domicile on the request to establish a quorum for the Third GMS (c) Article 78 paragraph (4) of Law No. 40 of 2007 that other GMS may be held at any time based on the need for the benefit of the Company (d) Article 22 paragraph 2 of the Articles of Association of PT Exploitasi Energi Indonesia, Tbk that the Second GMS is valid and has the right to make binding decisions if attended by shareholders who are representing at least 1/3 (one-third) of the total number of shares with valid voting rights (d) Because from 2021-2023 PT Exploitasi Energi Indonesia, Tbk could not hold the EGMS due to lack of quorum, the Panel of Judges deemed it necessary to hold other EGMS to accommodate the impasse experienced by the Company. The above legal considerations can explain the decision of the Panel of Judges which applies the Principle of Lex Superior Derogate Legi Inferiori in the implementation of EGMS in Public Companies which is final and has permanent legal force in accordance with article 86 paragraph 7 of Law No. 40 of 2007.